KINETIKA REAKSI ESTERIFIKASI MINYAK BIJI KAPUK PADA PEMBUATAN BIODIESEL - Salamah, Siti (Universitas Ahmad Dahlan, 2014)
Biodiesel is one of the best solutions to overcomethe reduction of oil reserves by utilizing plant oils are converted into fuel.Kapok seed is one of the potential sources of raw materials that can be taken to be used as biodiesel. For the manufacture of biodiesel on a large scale is necessary to design the reactor, the reactor needs to design the data of reaction kinetics.This reaserch was conducted to determine the rate of reaction of biodiesel production. The process was by making kapok seed oil and analyzed the content of FFA, if FFA <2 then the esterification process is done.150 ml oil inserted in three neck flask and heated to temperature of 50 °C with water bath.While waiting for heating, 57 ml of techinical methanol 96 % was mixed with 1.25 grams KOH p.a and stirred for 60 minutes, then either mixing the solution with the oil heated with a water bath. The reaction temperature was maintained at 50oC with stirring speed of 600 rpm for 60 minutes. Inserting the solution into a separator funnel and left for 24 hours to form 2 layers.Separating the two layers.The top layer wasbiodiesel and the bottom layer was glycerol.Repeating step by step above with the variation of time 60, 75, 90, 105 and 120 minutes. For reaction temperature variable, the process carried out at temperatures 40 °C, 50 °C, 70 °C and 90 °C.The results of this reaserch were the water content of kapok seed is 4,07 % and FFA valuewas 4,8 % after lowered 1,56 %.Transesterification reaction conditions of oil and methanol mole ratio of 1 : 3, with the stirrer rotation speed of 600 rpm for 105 minutes and the reaction temperature of 90 °C gave the conversion of 0.916 mol (%).Transesterification reaction of kapok seed oil into biodiesel follows the first order reaction.The results of the analysis of biodiesel and the heat test, may indicate that it meets the criteria specified in the benchmark Indonesian Biodiesel Quality Standards (RSNI EB 020 551).